Peran Sertifikasi Halal terhadap Daya Saing UMKM Kuliner di Kabupaten Pasuruan - Nuril Ainiya; Alimatul Farida; Muhammad Nizar (Kartika: Jurnal Studi Keislaman, 2026)
Increasing business competition requires culinary MSMEs to improve their competitiveness. One way to improve MSME performance is by obtaining halal certification. In reality, many culinary business owners still see the halal certificate as just paperwork. Yet this document actually helps build buyer trust and adds selling value to products. Previous research also shows mixed results about how much the halal label affects small business competitiveness. Because of this gap, this research tests the impact of halal certification on culinary MSMEs in Pasuruan Regency. The approach was quantitative with 86 food business owners as respondents. Data were processed in SPSS through validity, reliability, descriptive, simple regression, t-test, and R Square tests. Findings reveal that halal certification has a positive impact on competitiveness. The significance was 0.002, below 0.05, with an effect contribution of 10.9%. indicates that halal certification influences the competitiveness of culinary MSMEs. Therefore, halal certification plays a crucial role in boosting the competitiveness of culinary MSMEs